Synthesis of carbon nanotubes and their application in TiO2 photocatalysis - Everhart, Brian M. (Kansas State University, 2022)
In the 21st century, scientists and engineers are tasked with furthering technological innovation while simultaneously achieving environmental sustainability. This necessitates the scalable development and implementation of advanced materials. The following work includes insight into the growth of single wall carbon nanotubes (SWCNTs) which are desired for a wide array of applications due to their exceptional, tunable properties. It also explores the use of composite materials comprised of CNTs and titanium dioxide (TiO₂) for environmental remediation applications. The research presented in this document establishes the ability of FTS-GP (Fischer Tropsch Synthesis Gas Precursor, a waste product of industrial processes) to generate water in situ via gas phase reaction of CO with H₂. The work demonstrates that this generated water is responsible for prolonged catalyst lifetime compared to a conventional precursor such as ethylene (C₂H₄). Experiments from both a conventional chemical vapor deposition (CVD) system and an autonomous research system (ARES) are supported by thermodynamic analysis, which together provide insight into the role of FTS-GP in generating on-site water during growth of SWNCT carpets. SWCNT growth is further investigated using Ru as a promoter to increase the selectivity of small-diameter SWCNTs (diameters below 1 nm). By performing over 200 growth experiments in ARES with different feedstocks and extensive multi-excitation Raman spectroscopic characterization, we demonstrate that the Ru-promoted Co catalyst doubles the selectivity of small-diameter SWCNTs (diameters below 1 nm) at 750 °C in comparison to Co, increasing to a factor of three at higher temperatures. Density functional theory (DFT) calculations with 13 and 55 atom Co[subscript x]Ru[subscript y] clusters (ranging from 0 to 22% Ru content) reveal increases in cluster cohesive energies (E[subscript C]) with Ru content. As these findings are indicative of increases in melting temperature and reduction in atom mobility with Ru content, they are consistent with the presence of ∼10% Ru in our Co catalyst which increases sintering resistance and stability of small nanoparticles, resulting in high selectivity toward small-diameter SWCNTs. After the discussion on SWCNT growth, the work in this document examines the fabrication of CNT-TiO₂ composite materials and their ability to efficiently eliminate airborne pollutants. It begins with the synthesis of CNT-TiO₂ composites and the role of CNTs in degradation of acetaldehyde, a representative volatile organic compound (VOC) in a batch reactor. The study indicates that a small amount of multi-walled carbon nanotubes (MWCNTs) increases catalyst performance compared to TiO₂, whereas the addition of CNTs beyond the optimum loading ratio of 1:100 (MWCNT:TiO₂) diminishes the effectiveness of the photocatalyst and the synergistic effect between MWCNTs and TiO₂. CNT-TiO₂ photocatalyst composites are subsequently implemented for degradation of NO[subscript x] in a continuous flow reactor. This study demonstrates the use of CNT-TiO₂ photocatalyst films for effective transformation of NO[sunscript x] into nitrates. Using the objective figure of merit for NO[subscript x] abatement, DeNO[subscript x] index, the catalyst performance in a laminar-flow reactor was evaluated under different conditions, including relative humidity (RH), initial NO[subscript x] concentration, reactor geometry (headspace distance), and state of the catalyst (fresh vs. recycled). Our results reveal CNT-TiO₂ significantly outperforms P25 in a humid environment despite exhibiting comparable NO conversion at low RH. In addition, mass transfer from the bulk airflow limits NO conversion when the reactor headspace is too large (>3 mm), due to limited diffusion of NO[subscript x] to the photocatalyst surface. The remarkable DeNO[subscript x] activity of CNT-TiO₂ over a wide range of RH levels is rationalized based on the ratio of physisorbed-to-chemisorbed water on the photocatalyst surface and the effect of this physisorbed water in increasing the amount of superoxide (O₂[supersript •-]) radicals generated.
Keywords: Photocatalysis; Carbon nanotubes; Nanomaterials; Environmental remediation